MODEL PEMBERDAYAAN MASYARAKAT DI AREA TERDAMPAK PENAMBANGAN PASIR BESI [COMMUNITY EMPOWERMENT MODEL IN THE IMPACTED AREAS OF IRON SAND MINING] - Firman Zulpikar; Syam Surya Syamsi (Universitas Pelita Harapan, 2018)
Iron sand is one of the coastal natural resources that have high economic value, but the mining activities often have a negative impact on the community and the surrounding environment, such as iron sand mining activities in Buni Asih Village, Sukabumi District. Some of the negative impacts are air pollution, decrease in productivity of agricultural land around the mining area, fishing ground becomes farther away, and the mining machine vibration disturbs people activities. This problem can lead to conflicts of natural resources utilization if not addressed immediately. One of the ways to prevent conflict is through community empowerment with integrated and sustainable way. LPPM Surya University in cooperation with BP3IPTEK West Java Province conducted community empowerment activities with the theme of innovative farming and environmental rehabilitation. There are four activities implemented: (1) establishment of Community Training Center (CTC) as the facility for training skills and transfer of technology, (2) Agricultural training with the hydroponic system, (3) microalgae cultivation training, and (4) Greening the environment through planting of breadfruit. The results of the activities showed high enthusiasm and community participation. There were more than 100 people involved in various training held. Agricultural training is considered the most successful program with a high level of understanding, mastery of material and interest to apply the technology. This program will make the community more independent, adaptive to the changes in surrounding environment, and will be able to reduce the conflict potential of coastal resource utilization.